Simultaneous determination of plasma indoles by HPLC with fluorescence detection: Application in polycystic ovary syndrome patients with/without depression. Issue 1 (25th February 2022) - Yang, Ke; Chen, Ying; Xiaoqing, Zhang; Zhen, Qianna; Gui, Wenwu; Ban, Yanna; He, Yifan; Pan, Shengnan; Ding, Min
Abstract: Microbiota-derived indoles were closely associated with psychological disorders like depression. We aimed to develop an HPLC method with fluorescence detection (FLD) for simultaneous determination of plasma indoles, including indoxyl sulfate (3-INDS), indole-3-acetic acid (IAA), indole-3-propionate (IPA), indole (IND) and 3-methylindole (3-MI). Diethyl ether and ethyl acetate were selected as the mixed extractant for the sample preparation. The separation was carried out on a Shim-Pack VP-ODS column (150 × 4.6 mm, 4.6 µm) with the mobile phase composed of 10 mmol/L sodium dihydrogen phosphate/methanol (40:60, v/v). The excitation and emission wavelengths were set at 280 and 355 nm, respectively. The linearities in plasma were obtained in the range of 1.56–400.0 μmol/L for 3-INDS, 0.312–10.0 μmol/L for IAA, 0.125–6.00 μmol/L for IPA, 6.25–400.0 nmol/L for IND, and 1.56–400.0 nmol/L for 3-MI, respectively. The coefficients of variation (CVs) for each analyte of the intra-day and inter-day precisions were within 4.0 and 5.2%, respectively. The recoveries were in the range of 90.1–109.3%. This sensitive and accurate method was applied to analyze plasma indoles for the diagnostic of depression in the patients with polycystic ovary syndrome (PCOS). Graphical Abstract: UF0001